Modified versions of ML-KEM based on Brazilian cryptographic resources - Lagrota, Vinícius; Azevedo, Beatriz L.; Filomeno, Mateus de L.; Ribeiro, Moisés V. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2024)
This paper outlines the Module-Lattice-Based Key-Encapsulation Mechanism Standard (ML-KEM) based on Brazilian cryptography to safeguard sensitive information. In this sense, it details two Brazilian cryptographic al gorithms, Forró and Xote, and discusses the modifications in the ML-KEM to enable their use as symmetric primitives. Relying on experimental results re garding execution time, we show that ML-KEM with Xote surpasses ML-KEM with SHAKE or Forró while maintaining an equivalent level of security in tasks such as key pair generation, encapsulation, and decapsulation.